Game-like situations training method and endurance impact on volleyball player performance - Risma, Nova; Umar, Umar; Bakhtiar, Syahrial; Ockta, Yovhandra (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to examine the impact of game-like situations training on the improvement of cardiovascular fitness and volleyball skills among high school students. The quasi-experimental design involved a sample of 32 secondary school students aged 13-17 years, divided into four groups based on two training methods (game-like situations and endurance) and two skill levels (high and low). The 8-week program, with sessions twice a week, focused on improving players' technical skills such as passing, setting, and ball control, as well as their cardiovascular endurance. Data were collected through the Yo-Yo Intermittent Recovery Test to measure cardiovascular fitness, alongside physical endurance tests. The results showed that the game-like situations training method was more effective than endurance training in improving volleyball skills, particularly for players with high skill levels. While endurance also played a significant role, combining game-like situations with endurance training yielded dual benefits, enhancing both technical skills and cardiovascular fitness. This study suggests that integrating game-like situations into volleyball training programs at the adolescent level is essential for the holistic development of players. Further research is recommended to explore additional factors influencing skill development and to assess the long-term impact of these training methods.